Efeito das condições climáticas e amostragem em parâmetros anatômicos da madeira de diferentes materiais genéticos de Eucalyptus - Silva, Renata Guilherme Cândido da (2025)
The productivity, basic density, and anatomical parameters of wood from species of the genus Eucalyptus are influenced by genetic and environmental factors. Understanding how these factors interact is essential for enhancing silvicultural strategies, selecting genetic materials, and increasing the efficiency of the forestry industry. This dissertation aimed to evaluate the effect of climatic conditions and sampling point on the variation of anatomical parameters of wood from different genetic materials of Eucalyptus, cultivated in three growth sites with varying degrees of aridity (São Paulo - MAI: -0.03; Bahia - MAI: -2.09; Maranhão - MAI: -3.27). To achieve this, 74 trees were sampled, with discs collected at positions 0, 25, 50, 75, and 100% of the commercial height and at DBH (1.3 m). In the first chapter, the influence of climatic conditions on productivity, basic density, and wood anatomy of 05 clones at six years of age was evaluated. Significant variations were observed among sites for all evaluated variables, with a strong correlation noted between the modified aridity index (MAI) and characteristics such as basic density, fiber dimensions, and vessel frequency. The least arid site (SP) showed higher productivity and more developed fibers, while increased aridity resulted in higher wood density and an increase in the Runkel index. Genotype x environment interaction was found to be crucial for clone adaptation and performance. In the second chapter, variation in the base to-top direction of anatomical characteristics was assessed, focusing on the representativeness of DBH and the development of predictive models. Fiber length and width and lumen diameter did not show a clear trend along the stem, while vessels exhibited a slight increase from base to top. Model analysis demonstrated that more accurate estimates of anatomical characteristics can be obtained by combining two to three sampling positions, reducing the need for sampling at all positions. These results underscore the importance of modeling and careful selection of sampling points for anatomical studies and industrial applications